Oracle bones, stars, and wheelbarrows ancient Chinese science and technology - Ross, Frank Xavier 1914- (Houghton Mifflin, 1982)
Discusses the achievements of the ancient Chinese in astronomy, medicine, science, and engineering, as well as such influential Chinese inventions as paper, printing, gun powder, and the compass.